Gestão de conhecimento, aprendizagem organizacional e inovação em empresas colombianas que adotam o teletrabalho - Beatriz Elena Hernandez Arias (2019)
Teleworking is a work-type activity that takes place off-site, supported by the use of information and communication technologies. This type of work allows network interconnection between companies and teleworkers. However, it is not clear how knowledge can be generated, shared and managed in companies that adopt this system. According to the literature, most research in the field of teleworking seeks to measure its impacts on mobility, wages, labor flexibility or productivity. However, few studies are focused on exploring the relationship of teleworking with knowledge management, learning or innovation in the company. This PhD research was funded with resources from the PAEC-OAS, CAPES program and aimed to analyze the adoption of knowledge management practices and tools in Colombian companies with teleworking. To perform it, a survey was conducted. Inferential statistics was used through a non-probabilistic sampling technique. The units of analysis were the employees of the Colombian companies that have signed the pact for teleworking with the Organización para el Teletrabajo. Likert scale applied to closed questions was used. Data analysis was based on multivariate statistics as it had two independent variables (knowledge management practices and technological tools for knowledge management) and two dependent variables (organizational learning and innovation). It is concluded that teleworking has advantages for both the company and the teleworker. Also, that there is a causal relationship between some knowledge management practices and tools with organizational learning and innovation. However, the flexibility of teleworking can negatively influence learning and innovation, especially knowledge sharing, as it needs direct communication between teleworkers and non-teleworkers.